An Updated Review on Some Neurotoxic Pharmacological Agents Along with their Neurotoxic Mechanisms (Indian Journal of Forensic Medicine & Toxicology, 2020)
This review will provide the vital information about some pharmacological agents which are Neurotoxic.Through this update, Anti-cancer, Anti-bacterial, Analgesic, Psychoactive drug and Anabolic steroidmedication are reported briefly regarding their neurotoxic mechanisms. In this review all informationregarding neurotoxic drugs is collected from 2020 published work by Web of science, Scopus, PubMed andGoogle Scholar. It is concluded that all these drugs which the part of our study are neurotoxic. There is needto discover some method to reduce their toxicity and to avoid the chronic use of these medications.
Keywords: Neurotoxic, Pharmacological agents, Anti-cancer, Analgesic, Antibacterial